On the fauna and ecology of hoverflies (Diptera, Syrphidae) of the Tarbagatai Ridge (Eastern Kazakhstan) - Zlatanov, B.V. (Fundamental and Experimental Biology, 2022)
The results of studies conducted in 2021 in some areas of the southern macroslope of the Tarbagatai Ridge, which are part of the Tarbagatai State National Natural Park, are presented. The purpose of the work is to identify the species composition of hoverflies in the national park and study their ecological characteristics. The studies were carried out according to generally accepted methods in entomology. The work was carried out on 2 sites located in the mid-mountain altitudinal landscape zone and 1 — in the small hills (the southern spur of the main ridge). 37 species of hoverflies belonging to 20 genera of 10 tribes of 3 subfamilies were identified. The local hoverfly fauna is heterogeneous both within one belt (middle mountains) and between belts (middle mountains/small hills). The similarity of faunas in the first case is 21.4%, in the second — 10.8%. Hoverflies were found on flowers of plants of 7 families: Brassicaceae, Rosaceae, Apiaceae, Aster-aceae, Rubiaceae, Scrophulariaceae, and Lamiaceae. The largest number of fly species was found on the family Apiaceae – 73.1%. In addition to flowering plants, a significant number of fly species (39.3%) were noted in other habitats, such as non-flowering plants and vegetative parts of flowering plants, on the ground, at a watering place, etc. The distribution and ratio of syrphid species depending on the food specialization of the larval phase were traced. Entomophagous dominate in all areas, represented mainly by species of the tribe Syrphini. The novelty of this work is due to the fact that hoverflies have not been studied in the Tarbagatai Ridge so far. The research results are significantly different from the data obtained by the author earlier in the Northern Tien Shan and the Dzungarian Alatau. Thus, it points out the great peculiarity of the ecological fea-tures of the local fauna of the syrphidflies of the region.